ON LINEAR INFINITE SYSTEMS OF DOMAIN-PRODUCT TECHNIQUE FOR WAVE SCATTERING PROBLEMS IN PLANAR WAVEGUIDE JUNCTIONS WITH RECTANGULAR CONNECTING CAVITY - Chumachenko, Y. V.; Chumachenko, V. P. (Radio Electronics, Computer Science, Control, 2011)
Properties of infinite systems of linear equations that occur when applying the domain-product technique to scattering problems for planar waveguide transformers with a loaded rectangular connecting cavity are studied. By the example of a waveguide bend, it is shown that in case of homogeneous Neumann conditions at conducting boundaries the method results in quasiregular systems.